2017
DOI: 10.1108/ijssp-07-2015-0074
|View full text |Cite
|
Sign up to set email alerts
|

Is there such a thing as too long childcare leave?

Abstract: Purpose The purpose of this paper is to revisit the question whether women’s employment is negatively affected in countries with very long periods of childcare leave. Design/methodology/approach The authors analyzed data on 192,484 individual women, 305 country-years, and 18-countries, combined with country-level data on childcare, unemployment and service sector size. Findings The authors found that in countries with short periods of childcare leave the motherhood-employment gap is smaller than in countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…An extensive literature beyond these seminal works has fueled the debate on paradoxes and tradeoffs (Bergmann 2009;Dieckhoff et al 2015;Kluve and Tamm 2013;Lalive and Zweimueller 2009;Morgan and Zippel 2003;Mun and Jung 2018;Nieuwenhuis et al 2017;Ziefle and Gangl 2015). For brevity, we review only a sample.…”
Section: The Paradoxes and Tradeoffs Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…An extensive literature beyond these seminal works has fueled the debate on paradoxes and tradeoffs (Bergmann 2009;Dieckhoff et al 2015;Kluve and Tamm 2013;Lalive and Zweimueller 2009;Morgan and Zippel 2003;Mun and Jung 2018;Nieuwenhuis et al 2017;Ziefle and Gangl 2015). For brevity, we review only a sample.…”
Section: The Paradoxes and Tradeoffs Hypothesismentioning
confidence: 99%
“…Consistent with claims of employer discrimination against women in countries with generous leaves, scholars have shown that Scandinavian countries tend to have high levels of occupational sex segregation (Charles and Grusky 2004). Much literature has scrutinized whether long parental leaves undermine women's careers (Morgan and Zippel 2003;Nieuwenhuis et al 2017). For example, Aisenbrey and colleagues (2009) found that in countries such as Sweden and Germany, long leaves hurt mothers' career attainment (also Evertsson and Duvander 2010; but see Keck and Saraceno 2013).…”
Section: The Paradoxes and Tradeoffs Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Paid parental leave facilitates the ability for parents, especially mothers, to continue their careers without completely withdrawing from the labour market. However, if the leave is too long, it can have negative consequences on women's employment (Nieuwenhuis et al, 2017).…”
Section: Literature and Hypothesesmentioning
confidence: 99%